Eavesdropper, not (only) reader. Transgressive possibilities of doubly deictic “you” - Puljić, Gabrijela (Poznańskie Studia Slawistyczne, 2025)
This article will take a closer look at the possible functions and stylizations of the use of the personal deictic “you” in the Croatian language. Since the double deixis manifests itself as a stylistic figure in its state of suspension – it is and is not a form of address – it is represented and exemplified by the so-called illocutionary overload as a (post-modern) discursive strategy that constructs the addressee and the audience. Narration or speaking in the second person singular will therefore serve as an illustration of (double) switches, a characteristic strategy for Tomičić’s drama for three voices, Don’t forget to cover your feet. It attempts to provide answers to questions such as: Does the reader have to be apostrophized to feel invited to participate in the discourse, does the present tense have to be a logical choice to achieve double deixis, what are signs of transition between the fictional and the real world in the Croatian language?